Pengenalan Dasar-dasar Investasi bagi Ibu-ibu PKK Kelurahan Babakan, Setu, Tangerang Selatan - Wiwit Irawati; Dea Annisa; Erika Astriani Aprilia; Tri Utami; Dila Angraini (S1 Accounting Program, Universitas Pamulang, 2019)
Investment is an important thing to do given the uncertainty in the future. Babakan Village is located in a position that makes it easy for people to be tempted to shop because of easy access to shopping centers. Through the PKK Mobilizing Team which is a government partner as well as a social organization that functions as a facilitator, planner, executor, as well as controller and with the aim of improving the welfare of the community, this PKM is held by providing counseling on the fundamentals of investment. PKM was attended by approximately sixty (60) participants of PKK ladies, the Secretary of the Village of Babakan and student representatives. This PKM has succeeded in fostering the enthusiasm and curiosity of participants to get to know the types of investments that are safe and can be done Key words: investment; PKK; investment risk; Babakan-SetuKeywords